O sentido da República em Esaú e Jacó, de Machado de Assis - Santos, Gilberto de Assis Barbosa [UNESP] (2015)
This dissertation has the objective to understand the sense of the representation that Machado de Assis does of the way of the monarchy until republic. The transposition of a historic fate for the fiction is at the penultimate romance that the chronicler published in 1904: Esaú and Jacó. Between others characters, in this narrative the readers will find characters that can impersonate there polarity between monarchists and republicans at the last decades of the empire that had been reeling from the final 60s of the XIX century. This analysis is based, especially, in the way how the events leading the disappearance of the reign Brazilian appears in this enunciation, so as to allow to readers understand the politic game that was in that time and how the partisan dances were maintained by the new regime, opened in the final of the Brazil nineteenth century